Life Cycle Assessment to Improve the Sustainability of Cylinder Head Component Production Process at PT XYZ - Yanti, Anti Novi Yanti; Kurniawan, Wawan Kurniawan; Marie, Iveline Anne Marie (JURNAL TEKNIK INDUSTRI, 2026)
The automotive industry is a significant contributor to environmental concerns. The automotive industry is also under increasing pressure to move towards sustainability due to its role in generating emissions and high energy consumption. As a result, it has an impact on environmental aspects such as air pollution, water pollution or other pollution obtained from industrial activities, which can be minimized so that it cannot become an environmental burden. To help analyze the environmental impact of the cylinder head manufacturing process, a Life Cycle Assessment is required. To support the company's sustainability, a sustainable index value is calculated based on three pillars: economic, environmental, and social. This research focuses on the casting, machining and assy engine processes. The primary objective is to identify the processes with the most significant environmental impact, thereby calculating the company's sustainable index value. This research employs the Life Cycle Assessment method, utilizing SimaPro software, to calculate the impact of the production process and determine the sustainable index (SI) based on the acquired impact value. The method used is EDIP 2003, with the impact categories analyzed, namely Human Toxicity Water, Aquatic Eutrophication EP, Adification, Ecotoxicity water. Based on the results obtained, the most significant impact among the four other impacts is Aquatic Euthropication with the most significant contribution to eletricity with a total value of 0.38938 GPt in the engine assy process. Based on the results obtained, alternative improvements can be suggested, such as the use of solar energy (solar panel system) and the utilization of carbon capture and storage technology, as well as other proposed improvement scenarios. With the implementation of the proposed scenario, the overall sustainable index value increases to 53.81% from 57.47% previously.